Meta-Synthesis, The Gig Economy: A Paradigm Shift in The Digital Transformation Era and Its Impact on Employment and National Development - Suhari (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This study investigates the paradigm shift in the gig economy during the digital transformation era by analyzing 140 scientific journals from 2016 to 2024. Five main themes are identified: economic stability, mobility, social and economic impacts, environmental impacts, and macroeconomic impacts. The findings show that the gig economy offers opportunities such as flexibility and inclusiveness, but also presents risks such as income uncertainty and worker exploitation. Policy recommendations include appropriate regulations, skills training, access to social security, transparency of digital platforms, and further research. With the right policy implementation, the gig economy can become an inclusive and sustainable economic model, contributing to fair and prosperous national development. A deep understanding of the dynamics of the gig economy is crucial in formulating appropriate policies to optimize its benefits and minimize its risks. Through the development of wise regulations and progressive policy innovations, we can create an environment where gig workers can work safely, decently, and sustainably. Moreover, investment in skills training and social support programs can help strengthen the position of gig workers in the ever-changing labour market. Thus, the gig economy can not only become a significant source of income for individuals but also contribute to inclusive and sustainable economic growth.